Kızılbaş and Nusayris in the Ottoman state, sixteenth-eighteenth centuries: accommodation in comparative perspective - Weineck, Benjamin (Islam and Christian-Muslim relations, 2024)
This article investigates the modes of interaction between the Ottoman state and the Kızılbaş and Nusayri communities in a comparative way. Both communities diverge from Hanafi-Sunnism, which was increasingly fashioned as the official Ottoman Islam in the course of the sixteenth century. Furthermore, both groups share a history of persecution, which has continued on and off until today and constitutes an important aspect of their respective identities. Yet persecution was but one side of the Ottoman treatment of both Kızılbaş and Nusayris: the state also integrated them into its administrative apparatus. Drawing on a variety of sources, this article seeks to identify different contexts in which the Kızılbaş and the Nusayris interacted with the Ottoman state and its local agents. The examples illustrate, on the one hand, how these groups were treated, labelled and thus perceived by the state and thereby accommodated to the Empire’s apparatus of power. On the other hand, they also indicate the historical agency of the groups themselves. The findings presented here thus serve to revisit the history of these communities in the Ottoman Empire, which has for long been approached from the perspective of their persecution as ‘heretics’.
Published online: 29 Jan 2024
Gesehen am 26.06.2024